PENGARUH TINGKAT PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN MOJOKERTO TAHUN 2000-2011 - DEVI BUDIARTI (Universitas Negeri Surabaya, 2014)
This study aims to find out the level of development of education and economic growth in Mojokerto regency from year 2000 to 2011 and to identify the effect of education level on economic growth in Mojokerto regency. The results of this study indicate that the economic growth in Mojokerto regency during the study period experiencing growth despite the growth is fluctuating where the highest growth occurred in 2011 at 7,14 percent . Growth of graduate education high school and university levels during the study period experienced significant growth which is the highest educational level dominated by of high school education compared to university because it is compulsory 9 years the government declared that the public was educated to high school level.. Education level affects economic growth in Mojokerto regency where high school education level have significant positive effect while the university have not a significant positive effect on economic growth in Mojokerto. Keyword : Education level, Economic growth.